Analysis of DNA binding and translocation by the E. coli CRISPR immunity protein Cas3 - He, Liu (2018)
Cas3 is essential for CRISPR-Cas immunity in Escherichia coli and is conserved across Class 1, type I CRISPR-Cas systems. Cas3 is a metal-dependent nuclease and ATP-dependent helicase that is required for CRISPR interference reactions, the stage of immunity in which a Cascade complex delivers crRNA to a complementary sequence in invader DNA to form an R-loop, trigger nuclease degradation of the invader, and stimulate adaptation (“priming”). Cas3 nuclease activity resides in an HD-domain (called Cas3’ here) and Cas3 translocation activity is catalysed by superfamily-2 helicase. The nuclease activity of Cas3 is crucial for interference and a preliminary analysis of its mechanism is presented here. We generated purified E. coli Cas3, Cas3’ and nuclease inactive Cas3’ proteins to study their activities on ssDNA and dsDNA substrates in comparison with similar substrates containing precisely positioned chemical modifications to the DNA backbone or bases. We observed that methyl-phosphonate and abasic DNA modifications had significant inhibitory effects on Cas3’ and Cas3 nuclease activities, and that there were some interesting differences in activities of these two enzymes when confronted with phosphorothioate DNA. This gives clues about the mode of action for Cas3’ and Cas3 when interacting with DNA for catalytic activity. The new work described will form the basis of more detailed kinetic analyses of Cas3’ and Cas3 nuclease activities in future work.